"Through the looking glass: envisioning new library technologies" spending time well – helping patrons take control of their technology. Issue 5 (2nd July 2018) - Fernandez, Peter
Abstract : Purpose: Social networking and mobile devices are now fully integrated into the fabric of society. Even people who do not directly use these applications are impacted by those who do. These technologies structure information, media companies, education, political policies and much more. Design/methodology/approach: At their best, these are technologies that can provide entertainment, increase productivity and improve the lives of their users. Findings: This column will explore concerns about how technology uses unconscious biases to influence its users' engagement. It will offer tools and techniques for those interested in exerting more control over their use of technology and how the underlying ecosystem has created this situation. Originality/value: It highlighted the work of Tristan Harris, who had previously worked at Google as a design ethicist but left to found an organization called Time Well Spent as one of the key leaders.